Adenosine deaminase inhibition suppresses progression of 4T1 murine breast cancer by adenosine receptor‐dependent mechanisms. Issue 12 (5th October 2018) - Kutryb‐Zajac, Barbara; Koszalka, Patrycja; Mierzejewska, Paulina; Bulinska, Alicja; Zabielska, Magdalena A.; Brodzik, Karolina; Skrzypkowska, Aleksandra; Zelazek, Lukasz; Pelikant‐Malecka, Iwona; Slominska, Ewa M.; Smolenski, Ryszard T.
Abstract: The activity of a cell‐surface ecto‐adenosine deaminase (eADA) is markedly increased in the endothelial activation and vascular inflammation leading to decreased adenosine concentration and alterations in adenosine signalling. Depending on the specific pathway activated, extracellular purines mediate host cell response or regulate growth and cytotoxicity on tumour cells. The aim of this study was to test the effects of adenosine deaminase inhibition by 2′deoxycoformycin (dCF) on the breast cancer development. dCF treatment decreased a tumour growth and a final tumour mass in female BALB/c mice injected orthotopically with 4T1 cancer cells. dCF also counteracted cancer‐induced endothelial dysfunction in orthotopic and intravenous 4T1 mouse breast cancer models. In turn, this low dCF dose had a minor effect on immune stimulation exerted by 4T1 cell implantation. In vitro studies revealed that dCF suppressed migration and invasion of 4T1 cells via A2a and A3 adenosine receptor activation as well as 4T1 cell adhesion and transmigration through the endothelial cell layer via A2a receptor stimulation. Similar effects of dCF were observed in human breast cancer cells. Moreover, dCF improved a barrier function of endothelial cells decreasing its permeability. This study highlights beneficial effects of adenosine deaminase inhibition on breast cancer development. The inhibition of adenosine deaminase activity by dCF reduced tumour size that was closely related to the decreased aggressiveness of tumour cells by adenosine receptor‐dependent mechanisms and endothelial protection.